2022
DOI: 10.3389/fnut.2022.873162
|View full text |Cite
|
Sign up to set email alerts
|

Higher Intake of Dietary Magnesium Is Inversely Associated With COVID-19 Severity and Symptoms in Hospitalized Patients: A Cross-Sectional Study

Abstract: Background and AimsMagnesium is an anti-inflammatory mineral that plays a role in the innate immune system, and the relaxation of bronchial smooth muscle warrants additional attention in COVID-19. This study examined the association between magnesium intake and COVID-19 severity and related symptoms in hospitalized patients.MethodsA cross-sectional study was done enrolling 250 COVID-19 patients aged 18 to 65 years. A validated 168-item online food frequency questionnaire (FFQ) was used to assess dietary magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…A study encompassing 250 Covid-19 patients aged 18 to 65 reported that individuals with an average age of 44 years experienced severe Covid-19, and these same patients exhibited low magnesium levels. The study further highlighted that increased dietary intake of magnesium correlated with a reduced likelihood of severe Covid-19 [45]. Conversely, the ndings of a recent study demonstrated that there is no substantial alteration in serum Mg levels between control subjects and Covid-19 cases [27].…”
Section: Differentiation Of Urinary Metal Excretion In Patients Of Di...mentioning
confidence: 79%
“…A study encompassing 250 Covid-19 patients aged 18 to 65 reported that individuals with an average age of 44 years experienced severe Covid-19, and these same patients exhibited low magnesium levels. The study further highlighted that increased dietary intake of magnesium correlated with a reduced likelihood of severe Covid-19 [45]. Conversely, the ndings of a recent study demonstrated that there is no substantial alteration in serum Mg levels between control subjects and Covid-19 cases [27].…”
Section: Differentiation Of Urinary Metal Excretion In Patients Of Di...mentioning
confidence: 79%
“…Similar findings have been shown in elderly patients that consume diets with low magnesium levels [ 32 ]. One could, therefore, speculate that magnesium intake might attenuate the severity of infectious diseases and this has been indeed proved in the clinical setting [ 30 , 33 , 34 ]. To date, unfortunately, in the field of obstetrics and particularly in cases with preterm premature rupture of the membranes, the beneficial effect of magnesium sulfate remains speculative as there is no evidence to support the pathophysiology behind this association.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there have been studies showing that patients with hypomagnesemia are most frequently hospitalized [ 89 , 115 , 117 , 119 , 120 , 121 ], and there have also been reports refs.~[ 57 , 116 , 120 , 122 , 123 ] of lower magnesium levels in severe cases of COVID-19 compared to less severe cases.…”
Section: Magnesium and Covid-19mentioning
confidence: 99%